Ultrastructural Changes During Pollen Wall Development and Germination in Arabidopsis Thalaiana - (:unkn) unknown (My University, 2016)
The Arabidopsis thaliana meiotic mutant 6491 has been identified as displaying temperature sensitive male reduced- fertility. It has been determined that callose wall formation is defective, both in temporal and structural areas. There is irregular rippling in the plasma membrane and aberrant formation of the exine portion of the pollen wall. A developmental study using brightfield, epifluorescence, and transmission electron microscopy of the early stages of wall formation in 6491 has been completed, along with a similar study of Arabidopsis thaliana (L.) heynh, ecotype Wassilewskija (WS). Due to the temperature-sensitive nature of the mutant line, a further study of both lines was completed at three different growth temperatures, all within the acceptable growth range of A. thaliana. Techniques for visualization included Hoffman modulation contrast microscopy to examine structure and aniline blue staining observed by epifluorescence microscopy to examine callose wall formation. Several potentially damaging structural differences were noted in both lines, dependent upon the temperature at which the plants had been grown. Further examination of pollen walls was undertaken, focusing on breakout of the pollen tube through the stiff patterned portion of the pollen wall layer known as exine. It has generally been accepted that pollen tubes exited through the interaperture space, where less biomechanical force would be required to breach the wall. However, it is now known that certain species of Arabidopsis thaliana are omniaperturate, breaking through the wall at a point closest in contact with the stigma. Pollen from a known omniaperturate line, Arabidopsis thaliana ecotype Landsberg erecta (Ler), was dusted onto male sterile-1 (MS-1) mutant plants in the same background. Brightfield and transmission electron microscopy were used to determine structural changes occurring within the grain and wall that would allow a pollen tube to breach such a resilient structure as exine.
Keywords: Arabidopsis Thaliana; Exine; Growth Temperatures; Heat Stress; Pollen Germination; Pollen Wall